A costomização em massa na construção civil, com foco na cadeia de suprimentos: um estudo no subsetor de edificações - Araujo Filho, João Tomé de (2009)
Mass customization is a relatively new business strategy and is used by organizations as a competitive differential in the conquest of new markets. This paper discusses the use of this strategy in constructions industry, especially in the subsection of buildings, in which elements of the conventional production coexist on the same work sites with elements of the customized production, performed according to the wishes and needs of each client, through individualized specifications (personalization). This study aims to verify how this process of mass customization and its reflection in the supply chain happen. It also verifies the application of the techniques of postponement as a prerequisite or facilitator agent in order to provide a product with the best possible expectations of each customer. The reason is in the importance of buildings subsection represents, both for the national economy as a whole and for the local economy in particular. As it is known, the importance and impact of this activity on the economic environment permeates the entire production chain and settles down starting from a complex relationship between the organizations. The methodology included bibliographical search and field research (exploratory and explanatory), held in three residential buildings, in the city of Campina Grande. It was found that using the techniques of postponement in the supply chain for mass customization is made up of a non-conscious, and despite the lack of terms and elements found in the literature. Its benefits, however, are seen clearly. The process of customization, on all three cases, was conducted in a similar way, but the final result was strongly linked to the purchasing power of their customers from each of the enterprises.